Characterization of electroforming-free titanium dioxide memristors - Strachan, John Paul; Yang, J. Joshua; Montoro, L. A.; Ospina, C. A.; Ramirez, A. J.; Kilcoyne, A. L. D.; Medeiros-Ribeiro, Gilberto; Williams, R. Stanley (Beilstein Journal of Nanotechnology, 2013)
Metal–insulator–metal (MIM) structures based on titanium dioxide have demonstrated reversible and non-volatile resistance-switching behavior and have been identified with the concept of the memristor. Microphysical studies suggest that the development of sub-oxide phases in the material drives the resistance changes. The creation of these phases, however, has a number of negative effects such as requiring an elevated voltage, increasing the device-to-device variability, damaging the electrodes due to oxygen evolution, and ultimately limiting the device lifetime. In this work we show that the deliberate inclusion of a sub-oxide layer in the MIM structure maintains the favorable switching properties of the device, while eliminating many of the negative effects. Electrical and microphysical characterization of the resulting structures was performed, utilizing X-ray and electron spectroscopy and microscopy. In contrast to structures which are not engineered with a sub-oxide layer, we observed dramatically reduced microphysical changes after electrical operation.
Keywords: electron microscopy; memristor; resistance switching; transition-metal oxide; X-ray spectroscopy

(untitled) - Chua, L. O. (IEEE Trans. Circuit Theory, 1971)

(untitled) - Chua, L. O.; Kang, S. M. (Proc. IEEE, 1976)

(untitled) - Strukov, D. B.; Snider, G. S.; Stewart, D. R.; Williams, R. S. (Nature, 2008)

(untitled) - Chua, L. O. (Appl. Phys. A, 2011)

(untitled) - Dearnaley, G.; Stoneham, A. M.; Morgan, D. V. (Rep. Prog. Phys., 1970)

(untitled) - Waser, R.; Dittman, R.; Staikov, G.; Szot, K. (Adv. Mater., 2009)

(untitled) - Liu, S. Q.; Wu, N. J.; Ignatiev, A. (Appl. Phys. Lett., 2000)

(untitled) - Sawa, A.; Fuji, T.; Kawasaki, M.; Tokura, Y. (Appl. Phys. Lett., 2004)

(untitled) - Szot, K.; Speier, W.; Bihlmayer, G.; Waser, R. (Nat. Mater., 2006)

(untitled) - Jeong, D. S.; Schroeder, H.; Waser, R. (Electrochem. Solid-State Lett., 2007)

(untitled) - Meijer, G. I. (Science, 2008)

(untitled) - Odagawa, A.; Sato, H.; Inoue, I. H.; Akoh, H.; Kawasaki, M.; Tokura, Y.; Kanno, T.; Adachi, H. (Phys. Rev. B, 2004)

(untitled) - Rozenberg, M. J.; Inoue, I. H.; Sánchez, M. J. (Appl. Phys. Lett., 2006)

(untitled) - Shoute, L. C. T.; Pekas, N.; Wu, Y.; McCreery, R. L. (Appl. Phys. A, 2011)

(untitled) - Lee, J. S.; Ortolani, M.; Schade, U.; Chang, Y. J.; Noh, T. W. (Appl. Phys. Lett., 2007)

(untitled) - Janotti, A.; Varley, J. B.; Rinke, P.; Umezawa, N.; Kresse, G.; Van de Walle, C. G. (Phys. Rev. B, 2010)

(untitled) - Jiang, W.; Noman, M.; Lu, Y. M.; Bain, J. A.; Salvador, P. A.; Skowronski, M. (J. Appl. Phys., 2011)

(untitled) - Janousch, M.; Meijer, G. I.; Staub, U.; Delley, B.; Karg, S. F.; Andreasson, B. P. (Adv. Mater., 2007)

(untitled) - Andreasson, B. P.; Janousch, M.; Staub, U.; Todorova, T.; Delley, B.; Meijer, G. I.; Pomjakushina, E. (Phys. Rev. B, 2009)

(untitled) - Jeong, H. Y.; Lee, J. Y.; Choi, S.-Y.; Kim, J. W. (Appl. Phys. Lett., 2009)

(untitled) - Martinez, E.; Guedj, C.; Calka, P.; Minoret, S.; Buckley, J.; Bernard, Y.; Jousseaume, V. (Surf. Interface Anal., 2010)

(untitled) - Calka, P.; Martinez, E.; Lafond, D.; Dansas, H.; Tirano, S.; Jousseaume, V.; Bertin, F.; Guedj, C. (Microelectron. Eng., 2011)

(untitled) - Fujii, T.; Arita, M.; Hamada, K.; Kondo, H.; Kaji, H.; Takahashi, Y.; Moniwa, M.; Fujiwara, I.; Yamaguchi, T.; Aoki, M.; Maeno, Y.; Kobayashi, T.; et al. (J. Appl. Phys., 2011)

(untitled) - Schroeder, H.; Pandian, R.; Miao, J. (Phys. Status Solidi A, 2011)

(untitled) - Kwon, D.-H.; Kim, K. M.; Jang, J. H.; Jeon, J. M.; Lee, M. H.; Kim, G. H.; Li, X.-S.; Park, G.-S.; Lee, B.; Han, S.; Kim, M.; Hwang, C. S. (Nat. Nanotechnol., 2010)

(untitled) - Strachan, J. P.; Pickett, M. D.; Yang, J. J.; Aloni, S.; Kilcoyne, A. L. D.; Medeiros-Ribeiro, G.; Williams, R. S. (Adv. Mater., 2010)

(untitled) - Yang, J. J.; Miao, F.; Pickett, M. D.; Ohlberg, D. A. A.; Stewart, D. R.; Lau, C. N.; Williams, R. S. (Nanotechnology, 2009)

(untitled) - Nauenheim, C.; Kuegeler, C.; Ruediger, A.; Waser, R. (Appl. Phys. Lett., 2010)

(untitled) - Borghetti, J.; Strukov, D. B.; Pickett, M. D.; Yang, J. J.; Stewart, D. R.; Williams, R. S. (J. Appl. Phys., 2009)

(untitled) - Pickett, M. D.; Strukov, D. B.; Borghetti, J. L.; Yang, J. J.; Snider, G. S.; Stewart, D. R.; Williams, R. S. (J. Appl. Phys., 2009)

(untitled) - Kilcoyne, A. L. D.; Tyliszczak, T.; Steele, W. F.; Fakra, S.; Hitchcock, P.; Franck, K.; Anderson, E.; Harteneck, B.; Rightor, E. G.; Mitchell, G. E.; Hitchcock, A. P.; Yang, L.; et al. (J. Synchrotron Radiat., 2003)

(untitled) - van der Laan, G. (Phys. Rev. B, 1990)

(untitled) - de Groot, F. M. F.; Figueiredo, M. O.; Basto, M. J.; Abbate, M.; Petersen, H.; Fuggle, J. C. (Phys. Chem. Miner., 1992)

(untitled) - de Groot, F. M. F.; Fuggle, J. C.; Thole, B. T.; Sawatzky, G. A. (Phys. Rev. B, 1990)

(untitled) - Strachan, J. P.; Yang, J. J.; Münstermann, R.; Scholl, A.; Medeiros-Ribeiro, G.; Stewart, D. R.; Williams, R. S. (Nanotechnology, 2009)

(untitled) - Soriano, L.; Abbate, M.; Vogel, J.; Fuggle, J. C.; Fernández, A.; González-Elipe, A. R.; Sacchi, M.; Sanz, J. M. (Surf. Sci., 1993)

(untitled) - Lusvardi, V. S.; Barteau, M. A.; Chen, J. G.; Eng, J., Jr; Frühberger, B.; Teplyakov, A. (Surf. Sci., 1998)

(untitled) - Pollakowski, B.; Beckhoff, B.; Reinhardt, F.; Braun, S.; Gawlitza, P. (Phys. Rev. B, 2008)